Market concentration, digital transformation, and bank credit risk in China: evidence from GMM estimation - YingShan Xu; Ainul Mohsein bt Abdul Mohsin; Fan Yang (Humanities & Social Sciences Communications)
Abstract The financial sector plays a pivotal role in fostering economic stability. Nevertheless, when compared to other countries, the credit risk associated with conventional commercial banks in China remains a notable concern. This study employs the Generalized Method of Moments (GMM) to examine this issue by analyzing data from 114 Chinese banks over the period from 2014 to 2021. The empirical evidence suggests that digital transformation has a significant and dynamic impact on reducing credit risks associated with banks. Additionally, market concentration appears to play an interactive role in this process. As market concentration increases, the risk-reducing effect of digital transformation is likely to diminish. Heterogeneity analysis shows that the impact is stronger in small and medium-sized banks, indicating that digital transformation has higher marginal governance benefits for banks with limited resources and capabilities. Subsequent interactive regression analyses indicate that bank market concentration significantly moderates the relationship between digital transformation and credit risk. In environments characterized by high market concentration, particularly among small banks, digital transformation exerts a more pronounced mitigating effect on non-performing loans. Conversely, in large banks, excessive market concentration may diminish the efficacy of strategic digitalization. Thus, banks may gain advantages by using market concentration to improve risk mitigation and achieve more precise risk evaluation. Policymakers ought to augment market regulation to guarantee a just competitive landscape, avert market monopolies, foster increased competition, and eventually mitigate credit risk.